2010
DOI: 10.1128/jcm.02319-09
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Identification of Zygomycetes Species from Paraffin-Embedded Tissues in a Murine Model of Disseminated Zygomycosis: a Collaborative European Society of Clinical Microbiology and Infectious Diseases (ESCMID) Fungal Infection Study Group (EFISG) Evaluation

Abstract: The present study was performed to assess the interlaboratory reproducibility of the molecular detection and identification of species of Zygomycetes from formalin-fixed paraffin-embedded kidney and brain tissues obtained from experimentally infected mice. Animals were infected with one of five species (Rhizopus oryzae, Rhizopus microsporus, Lichtheimia corymbifera, Rhizomucor pusillus, and Mucor circinelloides). Samples with 1, 10, or 30 slide cuts of the tissues were prepared from each paraffin block, the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 25 publications
0
61
0
2
Order By: Relevance
“…Four studies reported the development of PCR assays to diagnose the pathogens causing this disease (229)(230)(231)(232). An early study focused on the identification of Rhizopus spp.…”
Section: Pcrmentioning
confidence: 99%
“…Four studies reported the development of PCR assays to diagnose the pathogens causing this disease (229)(230)(231)(232). An early study focused on the identification of Rhizopus spp.…”
Section: Pcrmentioning
confidence: 99%
“…Fresh or frozen samples are preferred; however, based on recent inter-laboratory experimental and clinical data, formalin-fixed paraffin-embedded tissues may also be used. 26,27 Molecular identification of agents of mucormycosis can help to confirm diagnosis and identify the fungus to the genus and species level. Different techniques have been reported: DNA probes targeting 18S subunit, ITS1 sequencing after polymerase chain reaction (PCR) with pan-fungal primers, 18S-targeted semi-nested PCR and real-time PCR targeting cytochrome b gene.…”
Section: Category Grade Definitionmentioning
confidence: 99%
“…5,8,9,15,16 Although these molecular methods could detect species of a particular zygomycetes genus, they are limited by their detection range of pathogenic fungi, which is an important limiting factor in the context of diagnosis of invasive fungal infections. Further, the sensitivity of detection of fungal species by PCR or sequencing is very low in formalin fixed tissues compared to fresh tissues, 16 thus making diagnosis from fixed tissue section unreliable. More recently, to specifically identify species of fungi/zygomycetes, a combined approach of both morphologic and molecular testing methods have been explored when a histological diagnosis is not always possible.…”
Section: Introductionmentioning
confidence: 99%